Misoprostol for Prevention of Postpartum Hemorrhage at Home Birth in Afghanistan: Program Expansion Experience. (5th February 2016) - Haver, Jaime; Ansari, Nasratullah; Zainullah, Partamin; Kim, Young‐Mi; Tappis, Hannah
Abstract : Introduction: Afghanistan has a maternal mortality ratio of 400 per 100, 000 live births. Hemorrhage is the leading cause of maternal death. Two‐thirds of births occur at home. A pilot program conducted from 2005 to 2007 demonstrated the effectiveness of using community health workers for advance distribution of misoprostol to pregnant women for self‐administration immediately following birth to prevent postpartum hemorrhage. The Ministry of Public Health requested an expansion of the pilot to study implementation on a larger scale before adopting the intervention as national policy. The purpose of this before‐and‐after study was to determine the effectiveness of advance distribution of misoprostol for self‐administration across 20 districts in Afghanistan and identify any adverse events that occurred during expansion. Methods: Cross‐sectional household surveys were conducted pre‐ (n = 408) and postintervention (n = 408) to assess the effect of the program on uterotonic use among women who had recently given birth. Maternal death audits and verbal autopsies were conducted to investigate peripartum maternal deaths that occurred during implementation in the 20 districts. Results: Uterotonic use among women in the sample increased from 50.3% preintervention to 74.3% postintervention. Because of a large‐scale investment in Afghanistan in training and deployment of community midwives, it was assumed that all women who gave birth in facilities received a uterotonic. A significant difference in uterotonic use at home births was observed among women who lived farthest from a health facility (> 90 minutes self‐reported travel time) compared to women who lived closer (88.5% vs 38.9%; P < .0001). All women who accepted misoprostol and gave birth at home used the drug. No maternal deaths were identified among those women who used misoprostol. Discussion: The results of this study build on the findings of the pilot program and provide evidence on the effectiveness, primarily measured by uterotonic use, of an expansion of advance distribution of misoprostol for self‐administration.